Report of Working Group on International Dimensions, Government of India - Planning Commission (Planning Commission, 1998)
The National Commission constituted by the Ministry of Water Resources to prepare an Integrated Water Resources Development Plan (NCIWRDP), set up several Working Groups to deal with specialised areas within its terms of reference. Considering the major contribution of international rivers to the country's water resources, Working Group 9 was assigned to report on the International Dimensions of Integrated Water Resources Development. the Working Group comprised B.G. Varghese, Centre for Policy Research (Chairman); R.B. Shah, Ex-Chairman, Central Water Commission (CWC) ; R.P. Sinha, Chairman, Inland Waterways Authority of India (IWAI) ; R. Rangachari, Ex. Member, CWC ; T. Prasad, Professor, Patna University ; Dr. P.S. Rao, Jt. Secretary, Ministry of External Affairs (MEA) ; N.V.V. Char, Ex-Commissioner, Ministry of Water Resources (MOWR) ; Arbinda Ghose, Journalist and M.S. Menon, Ex- Chief Engineer, CWC (Resource Person). the Committee was assisted by a number of special invitees including Dr. M.A. Chital, Secretary General, International Commission on Irrigation and Drainage (ICID) ; Dr. C.D. Thatte, Secretary General, ICID ; S. C. Sud, Commissioner (Indus) MOWR ; A.C. Gupta, Commissioner (Indus) MOWR ; S.K. Das, Commissioner (Eastern Rivers) MOWR; Dr. V.G. Hegde, MEA and A.R. Ghatak, IWAI.
Report of Working Group on International Dimensions
Government of India